Пауки рода Drassodes (Aranei, Gnaphosidae) фауны Крыма - Ковблюк, Н.М. (Вестник зоологии, 2008)
По экземплярам из Крыма даны иллюстрированные описания и диагнозы 4 видов рода Drassodes Westring, 1851: D. lapidosus (Walckenaer, 1802), D. lutescens (C. L. Koch, 1839), D. pubescens (Thorell, 1856) и D. serratichelis (Roewer, 1928). Название D. macer (Thorell, 1875), syn. n. выведено из синонимии с D. cupreus (Blackwall, 1834) и сведено в синонимы к D. lapidosus. Из списка видов пауков фауны Крыма выведен D. cupreus. Впервые обнаружены самцы D. lapidosus без отростка на голени пальпы. Приведены сведения об ареале, фенологии и ландшафтном распространении в Крыму каждого из видов. Illustrated descriptions and diagnoses for 4 species of the genus Drassodes Westring, 1851: D. lapidosus (Walckenaer, 1802), D. lutescens (C. L. Koch, 1839), D. pubescens (Thorell, 1856) and D. serratichelis (Roewer, 1928) were made based on the specimens from Crimea. The name D. macer (Thorell, 1875), syn. n. was excluded from synonyms of D. cupreus (Blackwall, 1834) and recognized as a synonym for D. lapidosus. D. cupreus was excluded from the list of Crimean spider species. For the first time, males of D. lapidosus having no palpal tibial apophysis were described. Data on the distribution ranges, phenology and landscape distributions of each species in the Crimea were presented.